PENERAPAN METODE UCD UNTUK PERANCANGAN UI DAN UX DALAM MEMBANGUN FITUR MENTOR ON DEMAND DAN LIVE CHAT PADA WEBSITE SKILVUL - Youky Arie Sandi; Imam Ma’ruf Nugroho; Yudhi Raymond Ramadhan (P3M Institut Teknologi Pagar Alam, 2022)
The user interface (UI) plays an important role in giving the user a good initial impression of the visuals of an application or website. Meanwhile, User Experience (UX) helps build interaction between users and the application system or website. UI and UX design is very influential for user comfort, so it needs an accurate analysis according to user needs. Skilvul is a technology education platform that currently wants to create Mentor on Demand and Live Chat features. This feature is needed because the number of students is not proportional to the number of existing mentors, therefore this feature was created which aims to help Skilvul students to be able to consult and discuss learning with mentors privately. By making these features, UI and UX design will be carried out first using the User Centered Design (UCD) method. The results of the design in this study were carried out using the Single Ease Questionnaire (SEQ) method. Through the SEQ questionnaire, the average value is 6.5 where the value is included in the easy category. Based on these results, it proves that the results of UI and UX design in building Mentor on Demand and Live Chat features can be categorized as easy and according to user needs.